SMART CITIES: INTEGRATING SMART TECHNOLOGY IN CITY DEVELOPMENT IN THE ECONOMY 5.0 ERA - Loso Judijanto; Caroline, Caroline (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
In the Economy 5.0 era, the concept of smart cities is increasingly relevant with the integration of smart technology in urban development. Smart Cities emphasise the importance of using cutting-edge technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and big data analytics to improve the efficiency, safety, and quality of life of city dwellers. The implementation of this technology enables more effective management in various sectors, including transportation, energy, and health. However, the adoption of smart technology presents challenges such as cybersecurity, data privacy, and digital inequality, which require comprehensive attention and solutions through collaboration between the government, the private sector, and the community. With a holistic and collaborative approach, the integration of smart technology in city development can bring significant benefits to the sustainability and welfare of urban communities.